(untitled) (Semiárida, 2020)
Piptochaetium napostaense and Digitaria californica are codominant species of the mixed-grass prairie of the pampean calden forest, though only P. napostaense is important as a component of bovine’s diet. The winter burning of mixed-grass prairie would help to a better use of regrowths, mainly of summer species, and it could improve quality of deferred winter forage. The aim of this work was to evaluate the dynamic of leaf growth and leaf senescence of these species during spring and summer-fall regrowth, following a winter fire. The experimental units were composed by eight pairs of plants of both species, grown in representative plots of the mixed-grass prairie. The flux of leaf tissues were weekly estimated through the measurement of live blade and senescent blade lengths and, for each period, the total production of leaves and tillers were also estimated. During the first spring period after burning, D. californica and P. napostaense reached to the highest leaf blade net growth at low levels and two months earlier than the end of the rest period. Besides, at this time, the total number of leaves was also higher although P. napostaense tillering did not differed between years. Summer growth was always less than spring growth related to poor water conditions. In conclusion, the growth dynamics after burning shows that, for the semiarid conditions of the calden forest, D. californica and P. napostaense would stop dry matter accumulation at low biomass levels as they have both, low levels of net blade accumulation and tillering rates. Therefore, long rest periods after burning would lead to grassland deterioration through dead mass accumulation that, additionally, would depress summer species selectivity during winter deferred grassland utilization.